2014
DOI: 10.1177/0363546513518412
|View full text |Cite
|
Sign up to set email alerts
|

20 Years of Pediatric Anterior Cruciate Ligament Reconstruction in New York State

Abstract: This study quantifies the increasing rate of ACL reconstruction in the skeletally immature and suggests that there may be some disparities in care based on insurance status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
298
1
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(320 citation statements)
references
References 32 publications
14
298
1
7
Order By: Relevance
“…The study also revealed that diagnosis and reconstruction of pediatric ACL tears were rising at a rate significantly higher than that of adults [12]. These numbers were similar to that seen in a populationbased study from New York State that revealed that the rate of ACL reconstructions over the last 20 years has more than doubled in patients aged 3 to 20 years [13].…”
Section: Incidencesupporting
confidence: 75%
“…The study also revealed that diagnosis and reconstruction of pediatric ACL tears were rising at a rate significantly higher than that of adults [12]. These numbers were similar to that seen in a populationbased study from New York State that revealed that the rate of ACL reconstructions over the last 20 years has more than doubled in patients aged 3 to 20 years [13].…”
Section: Incidencesupporting
confidence: 75%
“…5,25,27,39 Many techniques have been described for ACL reconstruction in skeletally immature patients. 6,9,28 Transphyseal ACL reconstruction involves drilling bone tunnels across an open physis and fixing a soft tissue graft away from the physis.…”
mentioning
confidence: 99%
“…Nevertheless, this finding is consistent with a study conducted in Sweden which also showed that children aged below 10 years old account for less than 1% of total ACLR 4 . Maybe, this finding can be related with the fact that ACL tear is a rare injury in children 15,16 and generally surgeons prefer a conservative treatment for them due to the open growth plates that may be damaged during ACLR 17 . Surgery between those with 11 to 20 years old presented a significant increase over time; the same findings were seen in Sweden and the U.S. and can be explained by an increased participation in competitive sports by a youth population 4,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Maybe, this finding can be related with the fact that ACL tear is a rare injury in children 15,16 and generally surgeons prefer a conservative treatment for them due to the open growth plates that may be damaged during ACLR 17 . Surgery between those with 11 to 20 years old presented a significant increase over time; the same findings were seen in Sweden and the U.S. and can be explained by an increased participation in competitive sports by a youth population 4,17 . In our study, people aged between 21 to 40 years accounted for 2/3 of the total ACLR, most likely because of the high activity levels and participation in sports 9,18 .…”
Section: Discussionmentioning
confidence: 99%